Immediate implant placement into fresh extraction sockets versus delayed implants into healed sockets: A systematic review and meta-analysis - Mello, C. C. [UNESP]; Lemos, C. A.A. [UNESP]; Verri, F. R. [UNESP]; dos Santos, D. M. [UNESP]; Goiato, M. C. [UNESP]; Pellizzer, E. P. [UNESP] (Elsevier, 2017)
The aim of this systematic review and meta-analysis was to compare the survival rate of the implants and the peri-implant tissue changes associated with implants inserted in fresh extraction sockets and those inserted in healed sockets. This review has been registered at PROSPERO under the number CRD42016043309. A systematic search was conducted by two reviewers independently in the databases PubMed/MEDLINE, Embase, and the Cochrane Library using different search terms; articles published until November 2016 were searched for. The searches identified 30 eligible studies. A total of 3,049 implants were installed in a total of 1,435 patients with a mean age of 46.68 years and a minimum of 6 months of follow-up. The survival rate of delayed implants (98.38%) was significantly greater than immediate implants (95.21%) (p =.001). For the marginal bone loss (p =.32), implant stability quotients values (p =.44), and pocket probing depth (p =.94) there was no significant difference between the analysed groups. The immediate implants placed in fresh sockets should be performed with caution because of the significantly lower survival rates than delayed implants inserted in healed sockets.
Keywords: dental implants; fresh socket; healed socket; immediate implant; meta-analysis; systematic review